Cyber-attacks detection & protection in Kuwait government sectors - Alshaikhli, Imad Fakhri Taha; Al-Enezi , Khalid Abdulkareem; Al-kandari, Abdulrahman; Mahmood Al Dabbagh, Sufyan Salim (2014)
The world nowadays has witnessed a lot of crimes of cyber-attacks where many people suffered from many hackers who tried to steal important information or damage the programs found in the computers of victims. There has become necessity for companies to have different systems for protection. Many companies have been specialized in having systems for protection of these risks of hackers. Process of protection from cyber-attacks can be identified based on three main steps; reactive services, proactive services and security quality management. Such issues will be discussed in this research to help companies identify different risks against their computer systems to put an end to such attacks.